Integration of Artificial Intelligence in Learning to Improve Student Learning Outcomes at Sd N 42 Bengkulu City - Ziara Karunia Pratiwi; Niken Febiola; Andre Taulani Sandi; Pahrozi Ahmad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to describe the integration of Artificial Intelligence (AI) in learning and to illustrate the improvement in student learning outcomes in fifth grade at SD Negeri 42, Bengkulu City. This study used a qualitative, descriptive approach. Subjects included teachers and students selected through purposive sampling. Data collection was conducted through observation, interviews, and documentation. Data analysis employed an interactive analysis model encompassing data reduction, data presentation, and conclusion drawing. Its validity was tested through triangulation of sources and techniques. The results indicate that the integration of AI in learning creates a more interactive, adaptive, and engaging learning process, thereby increasing student activity, engagement, and understanding. Improved student learning outcomes are demonstrated by increases in class average grades and learning completion percentages. Several obstacles to implementing AI include limited devices, limited internet access, and the ability of teachers and students to use technology. Integrating AI into learning has significant potential to improve the quality of learning in elementary schools, but requires supporting facilities, teacher readiness, and ongoing development for optimal implementation.